Elucidating negative symptoms in the daily life of individuals in the early stages of psychosis. Issue 15 (22nd November 2021) - Hermans, Karlijn S. F. M.; Myin-Germeys, Inez; Gayer-Anderson, Charlotte; Kempton, Matthew J.; Valmaggia, Lucia; McGuire, Philip; Murray, Robin M.; Garety, Philippa; Wykes, Til; Morgan, Craig; Kasanova, Zuzana; Reininghaus, Ulrich
Abstract: Background: It remains poorly understood how negative symptoms are experienced in the daily lives of individuals in the early stages of psychosis. We aimed to investigate whether altered affective experience, anhedonia, social anhedonia, and asociality were more pronounced in individuals with an at-risk mental state for psychosis (ARMS) and individuals with first-episode psychosis (FEP) than in controls. Methods: We used the experience sampling methodology (ESM) to assess negative symptoms, as they occurred in the daily life of 51 individuals with FEP and 46 ARMS, compared with 53 controls. Results: Multilevel linear regression analyses showed no overall evidence for a blunting of affective experience. There was some evidence for anhedonia in FEP but not in ARMS, as shown by a smaller increase of positive affect ( B Δat−risk v. FEP = 0.08, p = 0.006) as the pleasantness of activities increased. Against our expectations, no evidence was found for greater social anhedonia in any group. FEP were more often alone (57%) than ARMS (38%) and controls (35%) but appraisals of the social situation did not point to asociality. Conclusions: Overall, altered affective experience, anhedonia, social anhedonia and asociality seem to play less of a role in the daily life of individuals in the early stages of psychosis than previously assumed. With the experience of affect and pleasure in daily life being largely intact, changing social situations and appraisals thereof should be further investigated to prevent development or deterioration of negative symptoms.